Effect of culture history and carbon sources on polyhydroxyalkanoates production in activated sludge systems - Ciftcioglu-Gozuacik, Bengisu; Pala-Ozkok, Ilke; Ubay-Cokgor, Emine (Taylor & Francis Ltd, 2024)
Polyhydroxyalkanoates (PHAs) are important and completely biodegradable alternatives to regular plastics, and they can be produced by activated sludge systems during wastewater treatment. Wastewaters with high organic content are being used for PHA production, which is an important resource recovery option. In this context, the effect of sludge retention time and different carbon sources, such as acetate, peptone-mixture and industrial wastewater (containing acetic acid (AA), lactic acid (LA) and propionic acid (PA)), on PHA storage was investigated. Oxygen utilisation rate (OUR) profiles were generated in respirometric tests and were evaluated by activated sludge modelling. Results showed that high storage (AA: 70%; LA: 49%; PA: 60% and industrial wastewater: 52%) was achievable in the feast phase even when the biomass was fed with a high organic acid content substrate to which it is not acclimated. [GRAPHICS]
Keywords: Mixed microbial culture; wastewater treatment; polyhydroxyalkanoates; respirometry; oxygen utilization rate